2018
DOI: 10.3389/fnins.2018.00792
|View full text |Cite
|
Sign up to set email alerts
|

Dbx1-Derived Pyramidal Neurons Are Generated Locally in the Developing Murine Neocortex

Abstract: The neocortex (NCx) generates at the dorsal region of the pallium in the forebrain. Several adjacent structures also contribute with neurons to NCx. Ventral pallium (VP) is considered to generate several populations of neurons that arrive through tangential migration to the NCx. Amongst them are the Cajal-Retzius cells and some transient pyramidal neurons. However, the specific site and timing of generation, trajectory of migration and actual contribution to the pyramidal population remains elusive. Here, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…These data were derived from the Allen Brain Atlas Data Portal (ABADP) resources available in the public domain: (http://help.brain-map.org/pages/viewpage.action?pageId=2424836). The data that support the findings of Figures 6 and 7 are based on the datasets partially published by García‐Moreno et al (2018; https://doi.org/10.1016/j.celrep.2017.12.032) and Rueda‐Alaña et al (2018; https://doi.org/10.3389/fnins.2018.00792) available from the corresponding author upon reasonable request. The data that support the findings of Figure 8 are based on the datasets published by Hoerder‐Suabedissen et al (2018; https://doi.org/10.1093/cercor/bhy036) and available from the corresponding author upon reasonable request.…”
Section: Data Availability Statementsupporting
confidence: 71%
See 3 more Smart Citations
“…These data were derived from the Allen Brain Atlas Data Portal (ABADP) resources available in the public domain: (http://help.brain-map.org/pages/viewpage.action?pageId=2424836). The data that support the findings of Figures 6 and 7 are based on the datasets partially published by García‐Moreno et al (2018; https://doi.org/10.1016/j.celrep.2017.12.032) and Rueda‐Alaña et al (2018; https://doi.org/10.3389/fnins.2018.00792) available from the corresponding author upon reasonable request. The data that support the findings of Figure 8 are based on the datasets published by Hoerder‐Suabedissen et al (2018; https://doi.org/10.1093/cercor/bhy036) and available from the corresponding author upon reasonable request.…”
Section: Data Availability Statementsupporting
confidence: 71%
“…However, no direct lineage tracing study has been performed so far confirming this hypothesis. Our preliminary focal electroporation studies examining the VPall and LPall revealed no dorsally migrating subplate neurons from VPall and LPall electroporations in the embryonic mouse (Figure 6; García‐Moreno et al, 2018; Rueda‐Alaña, Martínez‐Garay, Encinas, Molnár, & García‐Moreno, 2018; García‐Moreno, Molnár unpublished observations). Since Puelles' hypothesis postulates a restricted early LPall origin of the dorsally migrating subplate neurons (Puelles, 2014), these experiments have to be repeated with selectively targeting LPall at early stages (E11).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Developmental studies, particularly those on combinatorial expression patterns of early regulatory genes in relation to the topological framework of the neural tube, have become extremely useful to unravel the brain morphoplan, with its basic divisions comparable across vertebrates (Nieuwenhuys and Puelles, 2016). The conclusions of this type of approach support that a large lateroventral part of the avian and reptilian pallium (called the dorsal ventricular ridge) derives from pallial embryonic divisions that gives rise to the pallial amygdala and other areas of the so-called piriform lobe in mammals (Puelles et al, 2000, 2017; Medina et al, 2011, 2017a; Abellán et al, 2013; Desfilis et al, 2018), a proposal also supported by results of fate mapping (Hirata et al, 2009; Soma et al, 2009; Waclaw et al, 2010; Bupesh et al, 2011; Puelles et al, 2016a; García-Moreno et al, 2018; Rueda-Alaña et al, 2018), tract-tracing studies (Bruce and Neary, 1995; Martínez-García et al, 2007), and more recently, by single-cell transcriptome (Tosches et al, 2018). In this account, we will review the different data pointing to the presence of a pallial amygdala-like region in the sauropsidian dorsal ventricular ridge, as well as the possible existence of an area comparable to the orbitofrontal cortex.…”
Section: Introductionsupporting
confidence: 54%